Catestatin as a Target for Treatment of Inflammatory Diseases - Muntjewerff, Elke M.; Dunkel, Gina; Nicolasen, Mara J. T.; Mahata, Sushil K.; van den Bogaart, Geert (Frontiers in Immunology, 2018)
It is increasingly clear that inflammatory diseases and cancers are influenced by cleavage products of the pro-hormone chromogranin A (CgA), such as the 21-amino acids long catestatin (CST). The goal of this review is to provide an overview of the anti-inflammatory effects of CST and its mechanism of action. We discuss evidence proving that CST and its precursor CgA are crucial for maintaining metabolic and immune homeostasis. CST could reduce inflammation in various mouse models for diabetes, colitis and atherosclerosis. In these mouse models, CST treatment resulted in less infiltration of immune cells in affected tissues, although in vitro monocyte migration was increased by CST. Both in vivo and in vitro, CST can shift macrophage differentiation from a pro- to an anti-inflammatory phenotype. Thus, the concept is emerging that CST plays a role in tissue homeostasis by regulating immune cell infiltration and macrophage differentiation. These findings warrant studying the effects of CST in humans and make it an interesting therapeutic target for treatment and/or diagnosis of various metabolic and immune diseases.